Педагогическое взаимодействие: условия эффективности - Nizhneva, Natal’ja Nikolaevna; Nizhneva-Ksenofontova, Nadezhda Leonidovna; Ksenofontov, Vladislav Anatol’evič (Linguodidactica, 2017)
Integrity of pedagogical process, pedagogical interaction and its types within the framework of holistic pedagogical process are analyzed. Pedagogical communication, its functions and stages; the teacher’s initiative in the process of management of pedagogical communication and factors that provide it; axiological basis of education, its humanistic character are described.